Olfactory asymmetric dysfunction in early Parkinson patients affected by unilateral disorder - Zucco, Gesualdo M.; Rovatti, Francesco; Stevenson, Richard J. (Frontiers in Psychology, 2015)
Introduction: Parkinson’s disease often first presents with asymmetric motor symptoms. A number of studies have now established that sensory deficits can also be similarly asymmetric. It is well established that Parkinson’s disease is associated with marked olfactory dysfunction, but whether this too present assymetrically is a currently contentious question. Methods: To address this, we recruited 12 early stage Parkinson patients with right-sided motor symptoms and compared them to 12 healthy age-matched controls on tests of olfactory identification and recogniton administered separately to each nostril. Results: Data analyses indicated that Parkinson patients performed worse with the left nostril on both tasks, while no nostril-related differences were observed for the healthy age-matched control group on the same comparisons. Conclusions: These findings support the idea that asymmetric deficits do extend into olfactory performance in Parkinson’s disease - as they do into other sensory domains - and we examine the possibility that they might be a particular feature of right-sided motor symptom presentation.